2015
DOI: 10.7150/ijbs.13132
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Transcriptional Profile Based on Muscle Fiber, Mitochondrial Respiratory Activity, and Metabolic Enzymes

Abstract: Skeletal muscle is a highly metabolically active tissue that both stores and consumes energy. Important biological pathways that affect energy metabolism and metabolic fiber type in muscle cells may be identified through transcriptomic profiling of the muscle, especially ante mortem. Here, gene expression was investigated in malignant hyperthermia syndrome (MHS)-negative Duroc and Pietrian (PiNN) pigs significantly differing for the muscle fiber types slow-twitch-oxidative fiber (STO) and fast-twitch-oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 77 publications
(84 reference statements)
1
31
0
Order By: Relevance
“…Association analysis revealed that the GSK3A Hin 1I and Msp I polymorphisms were significantly associated with loin muscle area, average back fat thickness, thorax-waist fat thickness, and buttock fat thickness31. In addition, the gene could influence the muscle-to-meat process via glycolysis, reduced pH, and pale color3233. The selection of the GSK3 gene may contribute to enhanced fat storage ability and relatively high intramuscular adipose content.…”
Section: Resultsmentioning
confidence: 99%
“…Association analysis revealed that the GSK3A Hin 1I and Msp I polymorphisms were significantly associated with loin muscle area, average back fat thickness, thorax-waist fat thickness, and buttock fat thickness31. In addition, the gene could influence the muscle-to-meat process via glycolysis, reduced pH, and pale color3233. The selection of the GSK3 gene may contribute to enhanced fat storage ability and relatively high intramuscular adipose content.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously shown the transcriptional signatures in muscle from these pigs to be related to metabolic properties and mitochondrial respiration 22 24 . Furthermore, we wanted to know the mtDNA variation of these pigs and investigate whether mtDNA variation preferentially modifies the expression of mitochondria-associated OXPHOS gene from both mitochondria and nuclear genomes.…”
Section: Introductionmentioning
confidence: 97%
“…Our previous research on muscle transcriptional profile has revealed numerous biological pathways significantly associated with muscle fiber type, mitochondrial respiratory activity and metabolic enzymes [ 18 ]. It is of interesting to further investigate how miRNAs are involved in energy metabolism by fine-turning gene expression.…”
Section: Introductionmentioning
confidence: 99%